Pelatihan Dasar Digital Marketing Pada UMKM Desa Kambangan Kabupaten Tegal - Sonhaji; Anom Susetyo AN , Haries; Sudibyo , Toto; Fitriani , Rizki; Dwi Cahyani , Amelia; Nurkhayati; Lestari , Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The development of industry 4.0 and digital transformation are currently the main keys to the movement of micro, small and medium enterprises (MSMEs) in Indonesia. However, they still face three complicated problems, namely the lack of digital literacy for marketing, the need for business capital and difficulties in logistics distribution. Market opportunities in the digital era appear to be increasingly open and will produce many benefits if only smart MSMEs transform to take advantage of digitalization trends. Digital marketing not only helps MSMEs increase sales, but also helps them build their brand, increase visibility and build better relationships